Improving efficiency and operator proficiency during percutaneous coronary interventions utilizing a standardized optical coherence tomography workflow. (20th January 2023) - Khuddus, Matheen A.; Darki, Amir; Padaliya, Bimal B.; West, Nick E. J.; Rapoza, Richard J.; Buccola, Jana; Amis, Gregory; Chehab, Bassem M.; Secemsky, Eric A.; ,
Abstract: Objectives: This study was designed to compare efficiency and quality metrics between percutaneous coronary intervention (PCI) procedures using optical coherence tomography (OCT) guided by a variable workflow versus a standardized workflow in a real‐world population. Background: The LightLab (LL) Initiative was designed to evaluate the impact of a standardized OCT workflow during PCI to address barriers to adoption. Methods: The LL Initiative was a multicenter, prospective, observational study. PCI efficiency data were collected from 1/21/19 to 1/8/21 from 45 physicians at 17 US centers. OCT‐guided PCIs were compared between baseline phase (variable workflow; N = 383) and the LL workflow utilization phase ( N = 447). The LL workflow uses OCT to assess lesion Morphology, Length and Diameter, and then optimize outcomes by correcting for Medial dissection, stent mal‐Apposition, and under‐eXpansion (MLD MAX). Matching based on propensity scores was used to control for differences between PCIs. Results: After propensity matching, 291 paired procedures were included. Integration of the LL versus variable workflow resulted in no difference in procedure time (51 min vs. 51 min, p = 0.93). There was a reduction in radiation exposure (1124 mGy vs. 1493 mGy, p < 0.0001) and contrast volume (160 cc vs. 172 cc, p < 0.001). The LL workflow decreased the proportion of underexpanded lesions (34% vs. 54%, p < 0.0001) and improved minimum stent expansion (85% vs. 79%, p < 0.0001). Number of noncompliant balloons used was reduced with the LL workflow. (2.0 vs. 1.7, p < 0.01). Conclusions: These data suggest that standardizing imaging with the LL workflow may overcome barriers to imaging and improve PCI outcomes without prolonging procedures. Condensed abstract: The LightLab (LL) Initiative was a real‐world, prospective, observational study designed to determine the impact of a prescribed optical coherence tomography (OCT) workflow on percutaneous coronary intervention (PCI) guidance in 17 US centers. In this analysis, use of a standardized OCT workflow improved efficiency and quality metrics, reduced product utilization during PCI, and was associated with changes in OCT utilization consistent with increased proficiency. These data suggest that standardizing imaging during PCI with the LL workflow has the potential to overcome barriers to imaging and improve PCI outcomes without prolonging procedures, which may result in greater adoption.